Comparing public and private providers: a scoping review of hospital services in Europe - Liina-Kaisa Tynkkynen; Karsten Vrangbæk (BMC, 2018)
Abstract Background What is common to many healthcare systems is a discussion about the optimal balance between public and private provision. This paper provides a scoping review of research comparing the performance of public and private hospitals in Europe. The purpose is to summarize and compare research findings and to generate questions for further studies. Methods The review was based on a methodological approach inspired by the British EPPI-Centre's methodology. This review was broader than review methodologies used by Cochrane and Campbell and included a wider range of methodological designs. The literature search was performed using PubMed, EconLit and Web of Science databases. The search was limited to papers published from 2006 to 2016. The initial searches resulted in 480 studies. The final sample was 24 papers. Of those, 17 discussed economic effects, and seven studies addressed quality. Results Our review of the 17 studies representing more than 5500 hospitals across Europe showed that public hospitals are most frequently reported as having the best economic performance compared to private not-for-profit (PNFP) and private for-profit (PFP) hospitals. PNFP hospitals are second, while PFP hospitals are least frequently reported as superior. However, a sizeable number of studies did not find significant differences. In terms of quality, the results are mixed, and it is not possible to draw clear conclusions about the superiority of an ownership type. A few studies analyzed patient selection. They indicated that public hospitals tend to treat patients who are slightly older and have lower socioeconomic status, riskier lifestyles and higher levels of co-morbidity and complications than patients treated in private hospitals. Conclusions The paper points to shortcomings in the available studies and argues that future studies are needed to investigate the relationship between contextual circumstances and performance. A big weakness in many studies addressing economic effects is the failure to control for quality and other operational dimensions, which may have influenced the results. This weakness should also be addressed in future comparative studies.